Does proprioceptive system stimulation improve sit-to-walk performance in healthy young adults? - Pereira, Marcelo P. [UNESP]; Pelicioni, Paulo H. S. [UNESP]; Lahr, Juliana [UNESP]; Gobbi, Lilian T. B. [UNESP] (Soc Physical Therapy Science, 2015)
[Purpose] Sit-to-walk performance is linked to proper proprioceptive information processing. Therefore, it is believed that an increase of proprioceptive inflow (using muscle vibration) might improve sit-to-walk performance. However, before testing muscle vibration effects on a frail population, assessment of its effects on healthy young people is necessary. Thus, the aim of this study was to investigate the effects of muscle vibration on sit-to-walk performance in healthy young adults. [Subjects and Methods] Fifteen young adults performed the sit-to-walk task under three conditions: without vibration, with vibration applied before movement onset, and with vibration applied during the movement. Vibration was applied bilaterally for 30 s to the tibialis anterior, rectus femoris, and upper trapezius muscles bellies. The vibration parameters were as follows: 120 Hz and 1.2 mm. Kinematics and kinetic data were assessed using a 3D motion capture system and two force plates. The coordinates of reflective markers were used to define the center-of-mass velocities and displacements. In addition, the first step spatiotemporal variables were assessed. [Results] No vibration effect was observed on any dependent variables. [Conclusion] The results show that stimulation of the proprioceptive system with local muscle vibration does not improve sit-towalk performance in healthy young adults.
Keywords: Sit-to-walk; Proprioception; Muscle vibration